Analysis of the relationship between sleep-related disorders and cadmium in the US population - Luo, Zhuanbo; Zhu, Ning; Xiong, Kunlong; Qiu, Feng; Cao, Chao (Frontiers in Public Health, 2024)
BackgroundCadmium is a heavy metal that accumulates in the body due to environmental and occupational exposure. The neurotoxicity of cadmium received increasingly attention in recent years. Sleeping is regulated and coordinated by nervous system, however, little is known about the relationship between cadmium and sleep. This study aimed to examine the relationship between blood cadmium concentrations and sleep-related disorders in US adults.MethodsThis cross-sectional study used data on blood cadmium and sleep from the 2005–2008 and 2015–2020 National Health and Nutrition Examination Survey (NHANES). Weighted multiple regression, generalized weighted modeling, and weighted restricted cubic splines (RCS) were utilized to investigate the association between blood cadmium and sleep outcomes (sleep duration, trouble sleeping, symptoms of obstructive sleep apnea (OSA) and daytime sleepiness). Furthermore, subgroup analyses were conducted to investigate any differences in the associations between age, gender, ethnicity, education level, marital status, smoking status, alcohol consumption, diabetes mellitus (DM), cardiovascular disease (CVD) and hypertension groups.ResultsIn 19,152 participants, the median blood cadmium concentration was 0.48 (IQR: 0.28, 0.82)μg/L. Compared with the lowest reference quartile, participants in the higher quartile had a significantly higher risk of insufficient sleeping (<7 h/night) in crude model (OR 1.53, 95% CI 1.33–1.74), Model 1 (OR 1.57, 95% CI 1.38–1.80) and Model 2 (OR 1.45, 95% CI 1.27–1.65). In the unadjusted model, individuals in the highest quartile of cadmium level had a significantly increased risk of OSA symptoms of 53% (OR = 1.53, 95% CI: 1.42, 1.65) compared with participants in the bottom quartile, and this risk increased by 35% (OR = 1.35, 95% CI: 1.23, 1.48) after adjusting for all covariates. Individuals in the highest quartile of cadmium level were 76% more likely to have a trouble sleeping than individuals in the lowest quartile in the unadjusted model (OR = 1.76, 95% CI: 1.31, 1.93), whereas in the fully adjusted model, this likelihood was 86% higher (OR = 1.86, 95% CI: 1.51, 1.96). A similar positive correlation was also observed for cadmium level and daytime sleepiness. However, no relationship was noted between cadmium and excessive sleep duration (≥9 h). A linear dose–response relationship was found between cadmium concentration and the risk of insufficient sleeping (P non-linearity = 0.321), OSA symptoms (P non-linearity = 0.176), trouble sleeping (P non-linearity = 0.682) and daytime sleepiness (P non-linearity = 0.565). Additionally, no significant interactions between cadmium concentrations and subgroup variables were identified (P for interaction>0.05).ConclusionInsufficient sleep, symptoms of OSA, trouble sleeping and daytime sleepiness were found to have a positive association with the blood cadmium concentration in US adults. However, further prospective studies are necessary to establish whether there is a causal relationship between these factors.